Understanding the Adoption of Healthy Mobile Diet Applications Among Adults - Rima Zakiah Putri; Betty Purwandari; Ni Wayan Trisnawaty (The Indonesian Journal of Computer Science, 2025)
Non-communicable diseases (NCDs) account for 53% of premature deaths globally, posing significant challenges to healthcare systems. In Indonesia, the rising prevalence of obesity and overweight among adults highlights the urgent need for innovative interventions to promote healthier lifestyles. Mobile diet applications have emerged as a promising solution, offering accessible tools for health monitoring and behaviour change. However, adoption rates in Indonesia remain low due to a limited understanding of the factors influencing user acceptance. This study aims to analyze the determinants of mobile diet application adoption among Indonesian adults using the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework, extended with five external factors: trust, perceived health threat, health consciousness, health conditions, and body image. Data were collected through an online survey with 218 respondents who had used diet applications such as Cronometer, FastEasy, and MyFitnessPal within the past six months. Partial Least Squares Structural Equation Modeling (PLS-SEM) was employed for analysis. The findings reveal that effort expectancy, social influence, price value, health conditions, and body image significantly influence adoption. In contrast, performance expectancy, hedonic motivation, trust, perceived health threat, and health consciousness were not significant predictors. These results underscore the importance of intuitive interface design, community-driven features, and personalization based on health data to enhance user engagement and adoption. This study contributes to understanding user behaviour in health technology adoption in a developing country. It offers practical recommendations for application developers and policymakers to optimize the use of mobile diet applications as part of broader efforts to address NCD challenges in Indonesia.